2015
DOI: 10.1002/srin.201400570
|View full text |Cite
|
Sign up to set email alerts
|

Study of Lattice Strain Evolution in Stainless Steel Under Tension: The Role of Self‐Consistent Plasticity Model

Abstract: The recently developed large strain elastic visco-plastic self-consistent (EVPSC) model, with various popular self-consistent schemes including the Affine, Meff, Secant, and Tangent, is used to study the lattice strain evolution in a stainless steel under uniaxial tension. The material parameters for the various self-consistent schemes are fitted to experimental stress and strain curve under uniaxial tension. An assessment of the predictive capability of the self-consistent schemes is performed based on compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…In this work, those modeling elements are incorporated into the elastic viscoplastic self-consistent (EVPSC) model [14,[22][23][24][25][26]. The EVPSC model has been successfully applied to study the evolution of internal elastic strain of stainless steel not exhibiting transformation [14,27], magnesium alloys [28][29][30] and zirconium alloys [31]. The polycrystal model is applied to interpret the hardening, texture and phase evolution during the insitu neutron diffraction measurement on the 304 stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, those modeling elements are incorporated into the elastic viscoplastic self-consistent (EVPSC) model [14,[22][23][24][25][26]. The EVPSC model has been successfully applied to study the evolution of internal elastic strain of stainless steel not exhibiting transformation [14,27], magnesium alloys [28][29][30] and zirconium alloys [31]. The polycrystal model is applied to interpret the hardening, texture and phase evolution during the insitu neutron diffraction measurement on the 304 stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…For a comprehensive discussion and comparison of the different linearization procedures the reader is referred to Lebensohn et al (2007). Different linearization schemes from Secant (stiff) to Tangent (compliant) linearization were explored (results not shown in the interest of space) and it was found that affine linearization (Masson et al, 2000) gave the best overall match for the observed response, similar to the findings of Wang et al,(2010) and Guo et al, (2015) Using the concept of Homogeneous Effective Medium (HEM) and enforcing stress equilibrium, the linearized grain level response and the aggregate response can be related using an interaction equation:…”
Section: The Vpsc Modelsupporting
confidence: 62%